A systematic literature review on the impact of artificial intelligence on workplace outcomes: A multi-process perspective - Pereira, Vijay; Hadjielias, Elias; Christofi, Michael; Vrontis, Demetris (My University, 2021)
Artificial intelligence (AI) can bring both opportunities and challenges to human resource management (HRM). While scholars have been examining the impact of AI on workplace outcomes more closely over the past two decades, the literature falls short in providing a holistic scholarly review of this body of research. Such a review is needed in order to: (a) guide future research on the effects of AI on the workplace; and (b) help managers make proper use of AI technology to improve workplace and organizational outcomes. This is the first systematic review to explore the relationship between artificial intelligence and workplace outcomes. Through an exhaustive systematic review and analysis of existing literature, we ultimately examine and cross-relate 60 papers, published in 30 leading international (AJG 3 and 4) journals over a period of 25 years (1995–2020). Our review researches the AI-workplace outcomes nexus by drawing on the major functions of human resource management and the process framework of ‘antecedents, phenomenon, outcomes’ at multiple levels of analysis. We review the sampled articles based on years of publication, theories, methods, and key themes across the ‘antecedents, phenomenon, outcomes’ framework. We provide useful directions for future research by embedding our discussion within HR literature, while we recommend topics drawing on alternative units of analysis and theories that draw on the individual, team, and institutional levels.
Keywords: Artificial intelligence; Workplace outcomes; Integrative framework; Systematic review